2017
DOI: 10.1097/jtn.0000000000000297
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Systematic Quality Improvement Process to Decrease Complications in Trauma Patients With Prehospital Peripheral Intravenous Access

Abstract: Peripheral intravenous (PIV) catheterization is commonly performed, and its complications are costly, may result in serious health issues, and may adversely affect patient satisfaction. At our large urban Level I trauma center, we identified a cluster of 7 PIV complications from prehospital insertions in a 5-month period. Several of the patients developed noninfectious as well as infectious, limb-threatening complications requiring aggressive operative intervention. A performance improvement project was charte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…More studies reported using implementation frameworks during study preparation ( n = 7, 26%) and delivery phase ( n = 7, 26%) than the evaluation phase ( n = 4, 15%). Nine implementation frameworks were identified in included studies, including the Practical Application of Clinical Evidence System (PACES) (Coomarasamy et al, 2014), Getting Research Into Practice (GRIP) (Coomarasamy et al, 2014; Gunasundram et al, 2021), Six Sigma initiative (DeVries et al, 2021), Promoting Action on Research Implementation in Health Services (PARIHS) (Forberg et al, 2016), Alberta Context Tool (ACT) (Forberg et al, 2016), Plan Do Check Act (PDCA) (Garrett, 2017), Behaviour Change Wheel (BCW) (Kleidon et al, 2019), Lean (Oh et al, 2020) and Kotter's Change Model (Stevens et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…More studies reported using implementation frameworks during study preparation ( n = 7, 26%) and delivery phase ( n = 7, 26%) than the evaluation phase ( n = 4, 15%). Nine implementation frameworks were identified in included studies, including the Practical Application of Clinical Evidence System (PACES) (Coomarasamy et al, 2014), Getting Research Into Practice (GRIP) (Coomarasamy et al, 2014; Gunasundram et al, 2021), Six Sigma initiative (DeVries et al, 2021), Promoting Action on Research Implementation in Health Services (PARIHS) (Forberg et al, 2016), Alberta Context Tool (ACT) (Forberg et al, 2016), Plan Do Check Act (PDCA) (Garrett, 2017), Behaviour Change Wheel (BCW) (Kleidon et al, 2019), Lean (Oh et al, 2020) and Kotter's Change Model (Stevens et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 27 included studies, the majority were quantitative in design ( n = 25, 93%) and conducted at a single site ( n = 25, 93%). Most of the studies were from the United States of America (USA) ( n = 12, 44%) (Boyar & Galiczewski, 2021; DeVries et al, 2016, 2021; Fakih et al, 2012, 2013; Garrett, 2017; Gilton et al, 2019; Oh et al, 2020; Platt & Osenkarski, 2018; Stevens et al, 2018; Taylor, 2015; Tofani et al, 2012) or Australia ( n = 7, 26%) (Cabilan et al, 2014; Hawkins et al, 2018; Keogh et al, 2020; Kleidon et al, 2019; Lim et al, 2020; Rhodes et al, 2016; Yagnik et al, 2017), with the remainder from Italy (Frigerio et al, 2012), Sweden (Forberg et al, 2016), Germany (Kampf et al, 2013), Spain (Mestre et al, 2013), Hong Kong (Chan et al, 2020), Taiwan (Chiu et al, 2015), Malaysia (Coomarasamy et al, 2014) and Singapore (Gunasundram et al, 2021). All studies were conducted in a hospital environment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation